Exploring international construction projects: Views from Malaysian construction firms / Che Khairil Izam Che Ibrahim … [et al.] - Che Ibrahim, Che Khairil Izam; Ayub, Abdul Rahman; Ahzahar, Nadira; Hassan, Siti Hafizan (Universiti Teknologi MARA, Pulau Pinang & and Pusat Penerbitan Universiti (UPENA), 2009)
The growing and expansion of the Malaysian construction sector into global arena remains high on the national agenda due to oversupply of Malaysian firms and the shrinking domestic construction market. This study focuses on the opinions of Malaysian construction firms in identifying the goals and benefits in exploring the international construction projects. Twenty eight (28) respondents from Class A and Grade 7 construction firms were studied to get their opinions on their willingness to expand into the international markets. The empirical results show profitability of the firm, introduction of operations method and establish market share are the most significant goals among the Malaysian construction firms in exploring international market. The findings also indicate that business expansion, prestige and stability are major benefits gained by undertaking international construction work. With regards to the willingness of Malaysian firms to expand internationally, it is found that Malaysian construction firms entirely support and encourage all the local firms to expand and explore the international construction contracts. The results of the study are of relevance to Malaysian construction firms as they illustrate the international construction goals and benefits in view to exploring international construction projects. This study has shown the possibility of Malaysian construction firms being recognised as global players. Hence, the success of the firms' incremental internationalization is expected to increase in the near future provided these firms can plan an excellent entry strategies decision making and get involved in international construction industry.